2017
DOI: 10.1007/s00429-017-1388-0
|View full text |Cite
|
Sign up to set email alerts
|

Neural pathways subserving face-based mentalizing

Abstract: Over the past few years, considerable progress has been done in clarifying the neural networks underlying mentalizing. However, although the cortical architecture of this function is relatively well understood, the white matter pathways that may be involved in conveying neural signals within the mentalizing network remain to be elucidated. To gain insight into this matter, a detailed stimulation mapping of face-based mentalizing was performed in 27 patients undergoing awake surgery for a right-sided diffuse lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 128 publications
2
48
0
Order By: Relevance
“…We found that more than half of the studies, particularly of the mirroring and mentalizing network, are based on clinical populations. They include major psychiatric and neurological disorders characterized by prominent social impairments, such as autism spectrum disorder (ASD) (Fishman, Datko, Cabrera, Carper, & Müller, 2015;Kana, Libero, Hu, Deshpande, & Colburn, 2014;Mueller et al, 2013), behavioral-variant frontotemporal dementia (Downey et al, 2015), and prosopagnosia (Gomez et al, 2015;Grossi et al, 2014;Song et al, 2015;Thomas et al, 2008Thomas et al, , 2009Valdés-Sosa et al, 2011), as well as those with secondary impairments in social cognition, such as schizophrenia (Fujino et al, 2014;Saito et al, 2017), amyotrophic lateral sclerosis (ALS) (Crespi et al, 2014(Crespi et al, , 2016, mild cognitive impairment (MCI) (Fujie et al, 2008), traumatic brain injury (Genova et al, 2015;Levin et al, 2011;Scheibel et al, 2011), Parkinson's disease (PD) (Baggio et al, 2012), brain lesion/stroke (Oishi et al, 2015;Philippi et al, 2009), velocardiofacial syndrome (Jalbrzikowski et al, 2014;Olszewski et al, 2017;Radoeva et al, 2012), multiple sclerosis (MS) (Mike et al, 2013) and diffuse low-grade glioma (Herbet et al, 2014;Herbet, Lafargue, Moritz-Gasser, Menjot de Champfleur, et al, 2015;Yordanova, Duffau, & Herbet, 2017). In terms of social cognitive measurements, the literature has employed several behavioral paradigms to probe each social function (see Table 1-3).…”
Section: Methodological Summarymentioning
confidence: 99%
See 3 more Smart Citations
“…We found that more than half of the studies, particularly of the mirroring and mentalizing network, are based on clinical populations. They include major psychiatric and neurological disorders characterized by prominent social impairments, such as autism spectrum disorder (ASD) (Fishman, Datko, Cabrera, Carper, & Müller, 2015;Kana, Libero, Hu, Deshpande, & Colburn, 2014;Mueller et al, 2013), behavioral-variant frontotemporal dementia (Downey et al, 2015), and prosopagnosia (Gomez et al, 2015;Grossi et al, 2014;Song et al, 2015;Thomas et al, 2008Thomas et al, , 2009Valdés-Sosa et al, 2011), as well as those with secondary impairments in social cognition, such as schizophrenia (Fujino et al, 2014;Saito et al, 2017), amyotrophic lateral sclerosis (ALS) (Crespi et al, 2014(Crespi et al, , 2016, mild cognitive impairment (MCI) (Fujie et al, 2008), traumatic brain injury (Genova et al, 2015;Levin et al, 2011;Scheibel et al, 2011), Parkinson's disease (PD) (Baggio et al, 2012), brain lesion/stroke (Oishi et al, 2015;Philippi et al, 2009), velocardiofacial syndrome (Jalbrzikowski et al, 2014;Olszewski et al, 2017;Radoeva et al, 2012), multiple sclerosis (MS) (Mike et al, 2013) and diffuse low-grade glioma (Herbet et al, 2014;Herbet, Lafargue, Moritz-Gasser, Menjot de Champfleur, et al, 2015;Yordanova, Duffau, & Herbet, 2017). In terms of social cognitive measurements, the literature has employed several behavioral paradigms to probe each social function (see Table 1-3).…”
Section: Methodological Summarymentioning
confidence: 99%
“…Benton tests, Philadelphia battery) (Gomez et al, 2015;Grossi et al, 2014;Thomas et al, 2008;Unger et al, 2016), and face memory tasks (e.g. Cambridge tests) (Gomez et al, 2015;Song et al, 2015;Unger et al, 2016); empathy was assessed by the "empathy quotient" (Chou et al, 2011;Herbet, Lafargue, Moritz-Gasser, Menjot de Champfleur, et al, 2015;Nakagawa et al, 2015;Takeuchi et al, 2013), the "interpersonal reactivity index" (Fujino et al, 2014;Parkinson & Wheatley, 2014), and the "trait emotional intelligence questionnaire" (empathy subsets) (Olszewski et al, 2017); mentalizing abilities were evaluated by "false belief" stories (Grosse Wiesmann et al, 2017), cartoon animations Scheibel et al, 2011), comic strip vignettes (Herbet et al, 2014;Kana et al, 2014), and the "reading the mind in the eyes" task (Anderson et al, 2015;Cabinio et al, 2015;Herbet et al, 2014;Mike et al, 2013;Yordanova et al, 2017). Such a wide variety of seemingly disparate disorders as well as diverse behavioral paradigms provide excellent opportunities for exploring the relationship between WM tracts and social functions.…”
Section: Methodological Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…It is in the elucidation of these higher-order functions that functional neuroimaging is most likely to advance the neurosurgical management of glioma patients. Recent work suggests that rs-fMRI 61 and DTI, 62 in conjunction with DES, may be able to map the networks and tracts involved in mentalizing tasks. Mandonnet et al similarly used rs-fMRI and DTI pre-and postoperatively to illustrate that resection of a right temporoparietal glioma disrupted a large-scale network involved in cognitive flexibility.…”
Section: Discussionmentioning
confidence: 99%